2011
DOI: 10.1038/mt.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

Several rAAV Vectors Efficiently Cross the Blood–brain Barrier and Transduce Neurons and Astrocytes in the Neonatal Mouse Central Nervous System

Abstract: Noninvasive systemic gene delivery to the central nervous system (CNS) has largely been impeded by the blood-brain barrier (BBB). Recent studies documented widespread CNS gene transfer after intravascular delivery of recombinant adeno-associated virus 9 (rAAV9). To investigate alternative and possibly more potent rAAV vectors for systemic gene delivery across the BBB, we systematically evaluated the CNS gene transfer properties of nine different rAAVEGFP vectors after intravascular infusion in neonatal mice. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
229
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 262 publications
(238 citation statements)
references
References 37 publications
5
229
0
1
Order By: Relevance
“…We used a gene therapy approach based on AAV9 to deliver LRMIS (16) in PDXa models as a feasible way to determine the percentage of patients responsive to MIS. The AAV9 serotype of the AAV family has been safely used to infect a range of cells and tissues, including cardiac myocytes (37), lung tissue (38), and neurons of the CNS and peripheral nervous system (17,(39)(40)(41)(42)(43), to correct a host of genetic diseases, including ALS (39, 40, 43), Parkinson's (44), Huntington's (45-51), and Sandoff (52). AAV9 has been shown to have enhanced tropism to muscles and neurons, high infectivity, and stable long-term expression, making it ideally suited for the treatment of tumors, where normal infected tissues (e.g., muscles) serve as a bioreactor-like source of therapeutic protein for long-term secretion into the circulation (53).…”
Section: Discussionmentioning
confidence: 99%
“…We used a gene therapy approach based on AAV9 to deliver LRMIS (16) in PDXa models as a feasible way to determine the percentage of patients responsive to MIS. The AAV9 serotype of the AAV family has been safely used to infect a range of cells and tissues, including cardiac myocytes (37), lung tissue (38), and neurons of the CNS and peripheral nervous system (17,(39)(40)(41)(42)(43), to correct a host of genetic diseases, including ALS (39, 40, 43), Parkinson's (44), Huntington's (45-51), and Sandoff (52). AAV9 has been shown to have enhanced tropism to muscles and neurons, high infectivity, and stable long-term expression, making it ideally suited for the treatment of tumors, where normal infected tissues (e.g., muscles) serve as a bioreactor-like source of therapeutic protein for long-term secretion into the circulation (53).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recent reports have shown that the central nervous system can be very effectively transduced via systemic administration [17][18][19] and the higher doses and use of self-complimentary vector genomes in these studies 20 may have contributed to this capability. These results suggest that improving the vector delivery system holds promise for enhancing retinal transduction while limiting the number of viral particles necessary to achieve sufficient levels of protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Foust et al [21] reported that AAV serotype 9 (AAV9) vectors could cross the intact BBB in neonates and adult mice and yield "widespread" transgene expression in astrocytes, neurons, and endothelial cells. This was followed by reports showing that this finding translated to non-human primates (NHPs) [47,48] and could be achieved with other AAV serotypes [49]. The term "widespread" to describe the transduction pattern of intravenously injected AAV9 may be confusing to those not involved in the field.…”
Section: Virus-based Systemsmentioning
confidence: 99%
“…The field of CNS gene therapy is evolving rapidly with the discovery of new viral vectors, mainly AAV capsids, with remarkable CNS tropism after vascular [21,36,49,[96][97][98], and CSF administration [18,36,47]. A large range of AAV capsids has been investigated for their CNS gene transfer properties by direct intracranial injection [99][100][101][102].…”
Section: Challengesmentioning
confidence: 99%